Fabrication of all glass microfluidic device with superior chemical and mechanical resistances by glass molding with vitreous carbon mold. (29th May 2019) - Haq, Muhammad Refatul; Kim, Young Kyu; Kim, Jun; Ju, Jonghyun; Kim, Seok-min
Abstract: A glass microfluidic device with superior chemical and mechanical resistance was fabricated using a cost-effective glass molding process with a vitreous carbon (VC) mold, which was prepared by the carbonization of a replicated polymer precursor. For the development of microfluidic chips with dense microchannels on a large footprint, a defect-free VC mold is essential. In this study, a furan imprinting process, in which a patterned furan layer was imprinted (cured) on a polished furan plate, was established to minimize warpage and gas bubble defects. In addition, the proposed imprinting process markedly reduced the fabrication time of the furan precursor. For feasibility testing, a glass micromixer with a total channel length of 30.6 cm and footprint of 20  ×  20 mm 2 was developed by glass molding with the VC mold and thermal fusion bonding. The fabricated glass-molded micromixer was durable at an internal pressure of ~24 MPa, and there was no swelling when used with toluene for an extended time.